2023-0285 EIB Investment Survey - European Union Overview - European Investment Bank (European Investment Bank, 2024)
This unique insight into the corporate investment in the European Union examines companies 39; finance needs and the constraints they face. The 2023 edition also provides insight into the pressing issues facing firms, such as climate change, high energy costs and the green transition. The survey, which has been administered since 2016, covers about 13 000 firms across the European Union, including a small sample of US firms.